Integrasi Kesatuan Di Tengah Kemajemukan Dalam Hidup Bermasyarakat: Eksposisi Teks Roma 14: 1-19 - Laturiuw, Dominggus; Sianipar, Rosmaida (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2024)
This article aims to find and explore an Integration of Unity in the midst of pluralism. The Researchers use Qualitative approach with the method of content analysis of biblical texts that are systematic to achieve this goal. The authors hope that through this content analysis research, we can find and integration Unity in the midst of Diversity. Through this research we hope it may contribute toward the building of Unity in the midst of Diversity, namely through Presenting Peace, a life that will build each other up and doesn't become a stumbling block for others people in the midst of the existing community life.